How expensive are post-traumatic stress disorders? Estimating incremental health care and economic costs on anonymised claims data - Tim Bothe; Josephine Jacob; Christoph Kröger; Jochen Walker (The European Journal of Health Economics, 2020)
Background: Post-traumatic stress disorders (PTSD) pose a high burden for individuals and societies. Although prevalence rates are rather low, high co-occurrence rates and overall impairments cause deleterious suffering and significant costs. Still, no long-term data on costs and trends in cost developments are available. Methods Claims data from a German research database were analysed regarding direct and indirect costs occurring for individuals with incident diagnoses of PTSD. Results were compared to non-exposed average insurants matched on age and gender. Costs were analysed over a 5-year period from 2~years preceding until 3~years following an incident diagnosis of PTSD. Results Overall costs for PTSD account for approximately 43,000~EUR per individual, which is three times higher than costs for non-exposed controls. Of these costs, 59% are caused by mental disorders, 18% specifically by PTSD. In the control group, costs for mental disorders account for 19% of total costs. Costs increase by 142% in the year after an incident diagnosis of PTSD but return to the initial level 2~years later. Still, costs are at least twice as high in every year as in those for the comparison group. Conclusions Individuals with PTSD seem to suffer from far more impairments in their general health conditions and incur many more costs than average insurants. Most of these seem to be caused by co-occurring mental disorders and show their maximum in the index year. Nevertheless, as costs decrease to their initial level, treatments seem to have counterbalanced the impairments due to PTSD. Thus, treatments for PTSD can be considered as beneficial and their cost-effectiveness should be further investigated.
Keywords: I18 (Public Health); I19 (Health – Other); 610; Post-traumatic stress disorders; Health care costs; Claims data; Cost-analysis; Cost-comparison